Analysis of Madrasah Management Patterns in Supporting The Quality of Education at MA Ponpes Al Iman Muntilan Magelang - Alfatchushodiqin; Mawardi, Imam; Imron (Urecol Journal. Part A: Education and Training, 2023)
Developed countries are shown through the quality of their human resources produced through education. Indonesia as one of the countries with the largest population in the world is heading towards becoming a big and advanced country through education. School based management (MBS) is an alternative in educational management that emphasizes in the school autonomy and creativity to improve the quality of education. This study aims to find out how the pattern of madrasah management supports the quality education at MA Ponpes Al Iman Muntilan Magelang. This study uses a qualitative approach with a descriptive method. The data collection techniques through questionnaires, interviews, observation, and documentation studies. In detail, the research results of each component in School-Based Management show: 1) 79.81% stated that curriculum management had been well managed and made a positive contribution to improving the quality of education, 2) 89.74% stated that student management had been well managed and provided positive contribution in improving the quality of education, 3) 84.62% stated that the management of facilities and infrastructurehad been well managed and made a positive contribution in improving the quality of education, and 4) 80.00% stated that financial management had been well managed and made a positive contribution in improving education quality. Thus as wholes, it shows that the majority of 83.54% stated that madrasah management can be managed properly and is by the principal implementing School-Based Management adjusted to the National Education Standards in supporting the quality of education at MA Ponpes Al Iman Muntilan Magelang.